PEDAGOGICAL TECHNOLOGY ON THE BASIS OF INFORMATIVE-COMMUNICATIVE MAPS: EXPERIENCE OF DEVELOPMENT AND USE AT THE LESSONS OF HISTORY - Svetlana G. Ostrizhnyaya (Russian State Vocational Pedagogical University, 2015)
The aim of the research is to check the efficiency of use of logicalstructural graph format while studying material in the form of informative-communicative maps (IC-maps) in formation of informative-communicative skills of pupils. Methods. Theoretical: analysis of means of pupils' informative-communicative skills formation in the process of learning activity, comparison of their possibilities for the study of school course of History; empirical: expert assessment of IC-maps (teachers of History are experts), experimental work on pupils' informative-communicative skills formation (forming experiment), supervising of the pupils' team work (work in groups) and assessment of the degree of importance and activity of their communicative interaction, surveying of pupils (self-assessment of received results), testing (success evaluation of studying material understanding); mathematical: statistical processing of surveying and testing results. Results. The efficiency of IC-maps use in the studying process is proved. More than 80% of pupils consider that the work with maps allow them to understand and memorize studying material better, communication culture increases due to the joint work with the map, skills of information structuring and generalizing are formed. Recommendations on IC-maps development and its use for humanitarian subjects are given for school teachers. Criteria of assessment of pupils' work with IC-map are developed. Scientific novelty. The new definition of «informative-communicative map» is introduced; own author interpretation as didactic means, having the form of structuring graph analogue of studying text and helping informative-communicative skills formation, creative thinking development and learning big amount of studying information are given. Methodological peculiarities of IC-maps use in the studying process and its possibilities of building on the basis of pedagogic technology of informative-communicative skills formation and creative thinking development are shown (mainly critical thinking). Practical significance. The research outcomes and results found in the process of experimental work can be used in the system of school education on its senior stage. Developed and proposed methodological recommendations and technological approach on the basis of IC-maps allow reaching significant results for informative-communicative skills formation of senior pupils and systematical learning of big amounts of studying information; its understanding within variety of scientific-historical interpretations and subjective opinions of pupils, appeared during their team work on IC-map. Proposed materials are included in the program «Methods of teaching History at school» for the History teachers' qualification improvement in the Tyumen State University.